Myocardial Ischemia-Reperfusion and Diabetes: Lessons Learned From Bedside to Bench - Dia, Maya; Paccalet, Alexandre; Pillot, Bruno; Leon, Christelle; Ovize, Michel; Crola Da Silva, Claire; Bochaton, Thomas; Paillard, Melanie (Frontiers in Cardiovascular Medicine, 2021)
In front of the failure to translate from bench to bedside cardioprotective drugs against myocardial ischemia-reperfusion, scientists are currently revising their animal models. Owing to its growing incidence nowadays, type 2 diabetes (T2D) represents one of the main risk factors of co-morbidities in myocardial infarction. However, discrepancies exist between reported animal and human studies. Our aim was to compare the impact of diabetes on cell death after cardiac ischemia-reperfusion in a human cohort of ST-elevation myocardial infarction (STEMI) patients with a diet-induced mouse model of T2D, using a high-fat high-sucrose diet for 16 weeks (HFHSD). Interestingly, a small fraction (<14%) of patients undergoing a myocardial infarct were diabetic, but treated, and did not show a bigger infarct size compared to non-diabetic patients. In contrast, HFHSD mice displayed an increased infarct size after an in vivo cardiac ischemia-reperfusion, together with an increased cell death after an in vitro hypoxia-reoxygenation on isolated cardiomyocytes. To mimic the diabetic patients’ medication profile, 6 weeks of oral gavage with Metformin in the HFHSD mice led to a similar extent of lower cell death after hypoxia-reoxygenation as in the standard diet group, compared to the HFHSD cardiomyocytes. Altogether, our data highlight that due to their potential protective effect, anti-diabetic medications should be included in pre-clinical study of cardioprotective approaches. Since diabetic patients represent only a minor fraction of the STEMI patients, diabetic animal models may not be the most suitable translatable model to humans, unlike aging that appears as a common feature of all infarcted patients.